Preliminary study about the inheritance of the carotenoids content in roots from cassava (manihot esculenta crantz) segregating populations (2012)
Vitamin A deficiency (VA/) is a major problem with huge public health implications. One strategy to overcome this problem is the development of varieties with increased levels of pro-vitamin A carotenoids. Cassava is a relevant crop in many regions of the world where VA/ is prevalent. Significant progress has already been achieved increasing the content of total carotenoids (CTC) in cassava roots. However, little is known about the inheritance of this trait in cassava. In this study the segregations for CTC in several full-sib and self-pollinated (S1) families were analyzed. Parent-offspring regression was used to estimate heritability, which was found into a high level ( and gt;0.60). The analyses of segregations did not allow for the identification of simple Mendelian patterns that could explain the variation in CTC in every family analyzed. However, enough evidence has been generated for a hypothesis that few (2-3) major genes control most of the variation in CTC but their action is modified by fe9 minor genes. Mounting evidence was also found that at least one single dominant gene may inhibit carotenoids accumulation in the roots.Key words: Carotene, cassava roots, genetic variability, inheritance.